Spherical Microstructures of Lu2O3:Ln3+ (Ln=Tm, Dy, Tb, Eu): Rapid Microwave‐Assisted Synthesis, Energy Transfer, and Multicolor Emission. Issue 18 (26th June 2017) - Wang, Yuexin; Liu, Wei; Song, Yanhua; Li, Yi; Zhou, Xiuqing; Sheng, Ye; Zheng, Keyan; Zou, Haifeng
Abstract: Lu2 O3 :Ln 3+ (Ln=Tm, Dy, Tb, Eu) microspheres have been synthesized via a rapid microwave route followed by annealing process. Diverse morphologies of samples can be easily realized by changing the volume ratio of H2 O/EtOH. The samples were characterized by scanning electron microscopy (SEM), X‐ray diffraction (XRD), fourier transform infrared spectroscopy (FT‐IR), thermogravimetry analysis (TGA). Under the excitation of UV light, Lu2 O3 :Ln 3+ exhibited the characteristic transitions of Ln 3+, and green (Tb 3+ ), blue (Tm 3+ ), red (Eu 3+ ), yellow (Dy 3+ ) light can be obtained. Under 360 nm irradiation ( 1 D2 ‐ 3 F4 transition of Tm 3+ ), both characteristic transitions of Tm 3+ and Dy 3+ can be observed in Lu2 O3 :1%Tm 3+, x %Dy 3+ samples. Furthermore, the critical distance between Tm 3+ and Dy 3+ was calculated, and the energy transfer process from Tm 3+ to Dy 3+ was dipole‐dipole interaction. This synthetic method may be useful for preparing other inorganic materials with multi‐color emitting. Abstract : Uniformed Lu2 O3 microspheres with diameter about 2 μm have been successfully synthesized via a facile and rapid microwave after heat treatment method. Lu2 O3 :Tb 3+ /Dy 3+ /Tm 3+ /Eu 3+ /Tm 3+ ‐Dy 3+ samples have good luminescent properties and present green, yellow, blue, red and white emissions. The energy transfer mechanism from Tm 3+ to Dy 3+ is dipole‐dipole interaction.